The utilities of the homes of a group of students from Suceava, Romania (One Health & Risk Management, 2023)
Introduction. The home is the environment in which family life takes place. Its quality depends a lot on the socio-economic situation of the family. In families where the material condition is increased, the number of rooms is at least equal to the number of family members. Moreover, the house has all the necessary equipment represented by electric light, adequate heating, running water supply and connection to the sewage system.Aim. To evaluate the living conditions of the families of the surveyed students; the type of housing and the number of living rooms in it; appreciation of the water supply method; knowledge of how to remove waste water; the heating mode of the house.Material and methods. The study was carried out on a group of 140 10th grade students from the Economic College (44 students), the Technical College (40 young people), the Sports High School (31 young people) and the Informatics College (25 teenagers) from Suceava. A questionnaire was applied to these young people with questions about their family home: its type, the number of rooms, the water supply, the connection to the electric light and the sewage system, and the heating method. The processing of the results on the collectives was carried out with the help of the Pearson test.Results. In the study group, most dwellings (80.00%) are of the house type. The number of rooms is mainly 5-6 (35.00%), but there are also houses with 7 to 12 rooms (32.14%). It is noteworthy the presence of 32.85% houses where the number of rooms is between 1 and 4, especially those in residential blocks. Special attention must be paid to the water supply system of these homes. Dominantly the water supply is from its own source extracted with the help of an electric pump (water pump with pressure tank) (38.57%) or directly through wells (33.57%). The connection to the central supply system is present only in 27.85% of cases. The differences calculated by collectives are statistically significant (p˂0.05). It is notable that a dominant percentage of the water supply with own installations of the families from the Sports College, while the use of well water predominates for those from the Informatics College. All houses are connected to electric light. The connection to the city's sewage system is present in 45.00% of cases. The existence of the own water supply installations is associated with an own system for the evacuation of waste and household water with their collection in an emptyable septic tank. Unfortunately, it is a system that does not fully meet the hygienic and sanitary requirements. Many times, the content of these septic tanks can infiltrate, affecting the quality of the soil and the water table. The heating of these houses is carried out mainly with the help of installations that use wood as fuel (57.14%), which can raise problems related to the uneven heating of the entire house. There are also 27.14% houses that are connected to the city's central heating system. The calculated differences are statistically insignificant for the collectives.Conclusions. A house with a large number of rooms is not mandatory and one in which the facilities are the best. Numerous problems arise related to the connection to the sewage system, which can raise numerous hygienic-sanitary problems.
Keywords: housing; running water; adolescents; sewage system